Effectiveness of a knee exercise intervention on knee osteoarthritis pain and severity in Buddhist monks receiving platelet-rich plasma injections: A quasi-experimental study: 10.55131/jphd/2025/230311 - Wongmak, Phetchanee; Wiwat Laochai; Rakchanoke Kotcharoen (Journal of Public Health and Development, 2025)
Knee osteoarthritis (KOA) is a prevalent condition affecting individuals across all age groups, resulting in pain, diminished physical functioning, and disability. This study aimed to determine the effects of the knee exercise intervention on reducing KOA symptoms and enhancing the physical functioning of a vulnerable group (Buddhist monks) who receive platelet-rich plasma injections. We hypothesized that the knee exercise intervention would help alleviate symptoms of KOA and improve the monks’ physical function. A two-group, pretest-posttest design quasi-experimental study was conducted. Sixty Buddhist monks were purposively selected from one hospital’s outpatient orthopedic department in Thailand. Eligible participants were randomly assigned to an experimental group (n = 30) and a control group (n = 30). The experimental group received the Knee Exercise Program as an intervention, while the control group underwent the usual outpatient care. Data were collected from August 2022 to November 2022. Osteoarthritis severity and pain intensity were measured at baseline and program completion (12-week post-test). Data analysis included descriptive statistics and dependent and independent sample t-tests. The results showed that the average age of the 60 participants was 65 years (range: 50–83 years). No significant group differences were found in any outcome measures at baseline. At program completion, the experimental group reported significantly decreased pain intensity (t = 5.66, p < .001), stiffness (t = 0.68, p < .001), improved physical functioning (t = 7.99, p < .001), and less severity in KOA than the control group (t = 4.19, p < .001). Therefore, the Knee Exercise Program is effective in alleviating KOA symptoms, reducing KOA severity, and improving physical functioning in patients with KOA receiving platelet-rich plasma injections. A large-scale randomized controlled trial with long-term follow-up is warranted